2016
DOI: 10.1016/j.biomaterials.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane vesicles decorated with glycolipid-anchored antigens and adjuvants via protein transfer as an antigen delivery platform for inhibition of tumor growth

Abstract: Antigen delivered within particulate materials leads to enhanced antigen-specific immunity compared to soluble administration of antigen. However, current delivery approaches for antigen encapsulated in synthetic particulate materials are limited by the complexity of particle production that affects stability and immunogenicity of the antigen. Herein, we describe a protein delivery system that utilizes plasma membrane vesicles (PMVs) derived from biological materials such as cultured cells or isolated tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…These findings are of particular relevance to studies using GPMVs for drug encapsulation (27,28), therapeutic targeting (26,27), and studies of membrane permeation (26,(29)(30)(31)(32). Our suggestion for possible approaches to avoid leakage in GPMVs may be of value therein.…”
Section: Discussionmentioning
confidence: 67%
“…These findings are of particular relevance to studies using GPMVs for drug encapsulation (27,28), therapeutic targeting (26,27), and studies of membrane permeation (26,(29)(30)(31)(32). Our suggestion for possible approaches to avoid leakage in GPMVs may be of value therein.…”
Section: Discussionmentioning
confidence: 67%
“…However, studies have shown that GPI‐anchored proteins can be enriched on the lipid rafts of exosomes without any alteration of their intrinsic functionality . Indeed, plasma membrane‐derived vesicles were recently developed for the delivery of antigens conjugated to GPI …”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissue was homogenized, and membranes were isolated by centrifugation over a 41% sucrose gradient. These TMVs were incorporated with immunoaffinity-purified murine GPI-B7-1 and GPI-IL-12 molecules (GPI-ISMs) by protein transfer [26]. GPI-ISM incorporation was confirmed by flow cytometry analysis using fluorochrome-conjugated antibodies.…”
Section: Tmv Vaccine Preparationmentioning
confidence: 99%
“…Briefly, cells isolated from in vivo studies were pre-incubated with Fc receptor blocking antibody in FACS buffer (PBS with 2% BCS, 5 mM EDTA, 0.05% sodium azide) at 4 • C for 10 min to block nonspecific binding of monoclonal antibodies to immune cells. Fluorochrome-conjugated primary antibodies were added and incubated for 30 min with shaking at 4 • C. Cells were washed three times with FACS buffer and analyzed the cells using a FACSCalibur, BD LSRII (BD Biosciences, San Jose, CA, USA) or a CYTEK Aurora (CYTEK, Fremont, CA, USA) flow cytometer [26,34]. Protein expression profiles of TMVs were also analyzed by staining with fluorochrome-conjugated antibodies after blocking the Fc receptors with Fc blocking antibody [26].…”
Section: Flow Cytometrymentioning
confidence: 99%